The role of mycorrhiza and humic acid on quantitative and qualitative traits of faba bean plant under different fertilizer regimes - Mirbakhsh, Mandana; Sohrabi Sedeh, Seyedeh Sara (Jurnal Ilmu Pertanian, 2023)
In sustainable agricultural ecosystem management, a key focus is on minimizing chemical fertilizer use and maximizing the use of non-chemical alternatives. Our study was designed to explore the impact of mycorrhizal fungi and humic acid (HA) on the quantitative and qualitative characteristics of faba beans under varying chemical fertilizer levels. The experiment involved different treatments, which included HA and mycorrhiza in four variations (control, HA, HA+ mycorrhiza, and mycorrhiza alone), and nitrogen, phosphorus, and potassium (NPK) fertilizers at three different dosages (50%, 75%, and 100% of the recommended amount). The findings revealed that combining HA with mycorrhiza significantly influenced root colonization, with the highest chlorophyll a concentration (1.58 mg g⁻¹) observed in the HA+ mycorrhiza treatment at 75% NPK. This treatment also led to the highest counts in seeds per pod, number of pods, and weight of 100 seeds. Between the 100% and 75% NPK levels in the HA+ mycorrhiza treatment, no significant differences were noted in terms of grain and biological yield. The greatest grain yields were measured at 4356 kg ha⁻¹ and 4322 kg ha⁻¹ for the HA+ mycorrhiza treatment at 100% and 75% NPK, respectively. Additionally, the highest concentrations of Fe, N, P, K, and Zn were observed with the HA+ mycorrhiza application at the 100% NPK level.